Psychopathological differences among three groups of school children affected by the war in Croatia - Šikić, Neven (Array, 1997)
The consequences of extreme violence such as war torture affect children in different ways and may immediately manifest at the physical and/or psychological level, or may remain hidden and unrecognized for years. The victims are usually very reluctant to speak about their traumatic experiences, and they often seek help for somatic problems. Taking these physical complaints seriously helps to progressively reach the psyhological effects of violence. Therefore, identification of these children should be directed to complete evaluation of their symptomatology and functioning. In this study rating scales and assessment instruments for children aged <15, such as CPRS with General Scoring Sheet (Fish, 1985) were used to assess the broad spectrum of psychopathology in this age group. These questionnaires were used in a large group of school children (N= 1888), 989 girls and 899 boys aged 7-16 years. The sample was divided into 3 groups: displaced, non-displaced and refugee children. Results showed that three groups significantly differ in 13 out of 15 psychopathological clusters. Discriminative analysis of three groups also showed significant differences. First discriminative function indicated depression, violence and antisocial behavior to be rare in non-displaced children, more prononced in displaced, and most pronounced in refugeee children. The second discriminant function showed hyperactivity, anxiety and psychosomatic disturbances to be rare in non-displaced children, more frequent in refugee, and most frequent in displaced children. These results indicate that war was very painful for a large group of children, among whom the displaced and refugee children are most affected by psychopathologic disturbances.